Cover Image, Volume 76, Issue 1. Issue 1 (9th December 2019) - Kunte, Nitish; McGraw, Erin; Bell, Sydney; Held, David; Avila, Luz‐Adriana
Abstract : The back cover image is based on the Review Article Prospects, challenges and current status of RNAi through insect feeding by Luz‐Adriana Avila et al., https://doi.org/10.1002/ps.5588 . Abstract : The back cover image is based on the Review Article Prospects, challenges and current status of RNAi through insect feeding by Luz‐Adriana Avila et al., https://doi.org/10.1002/ps.5588 .